Enhancing the Energy Efficiency of Wastewater Treatment Plants through Co-digestion and Fuel Cell Systems - Gandiglio, Marta; Lanzini, Andrea; Soto, Alicia; Leone, Pierluigi; Santarelli, Massimo (Frontiers in Environmental Science, 2017)
The present work provides an overview of technological measures to increase the self-sufficiency of wastewater treatment plants (WWTPs), in particular for the largely diffused activated sludge-based WWTP. The operation of WWTPs entails a huge amount of electricity. Thermal energy is also required for pre-heating the sludge and sometimes exsiccation of the digested sludge. On the other hand, the entering organic matter contained in the wastewater is a source of energy. Organic matter is recovered as sludge, which is digested in large stirred tanks (anaerobic digester) to produce biogas. The onsite availability of biogas represents a great opportunity to cover a significant share of WWTP electricity and thermal demands. Especially, biogas can be efficiently converted into electrical energy (and heat) via high temperature fuel cell generators. The final part of this work will report a case study based on the use of sewage biogas into a solid oxide fuel cell. However, the efficient biogas conversion in combined heat and power (CHP) devices is not sufficient. Self-sufficiency requires a combination of efficient biogas conversion, the maximization the yield of biogas from the organic substrate, and the minimization of the thermal duty connected to the preheating of the sludge feeding the anaerobic digester (generally achieved with pre-thickeners). Finally, the co-digestion of the organic fraction of municipal solid waste (OFMSW) into digesters treating sludge from WWTPs represent an additional opportunity for increasing the biogas production of existing WWTPs, thus helping the transition toward self-sufficient plants.